The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/ac402380h
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Mass Spectrometric Methods for the Determination of the Primary Products of Fast Pyrolysis of Carbohydrates and for Their Gas-Phase Manipulation

Abstract: Mass spectrometric methodology was developed for the determination and manipulation of the primary products of fast pyrolysis of carbohydrates. To determine the true primary pyrolysis products, a very fast heating pyroprobe was coupled to a linear quadrupole ion trap mass spectrometer through a custom-built adaptor. A home-built flow tube that simulates pyrolysis reactor conditions was used to examine the secondary reactions of the primary products. Depending on the experiment, the pyrolysis products were eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 44 publications
9
61
0
Order By: Relevance
“…The cellulosic and hemi-cellulosic fraction of pyrolysis oil vapors and condensed bio-oil is largely responsible for many of its adverse fuel properties and the high propensity for coke formation [1]. Studies on pyrolysis of cellulose and sugar-derived oxygenates coupled with gas or liquid chromatography (GC or LC) and mass spectrometry (MS) have shown how the small oxygenates formed during pyrolysis can undergo secondary polymerization reactions, forming larger molecules and eventually coke [17,18]. The composition of pyrolysis vapor and condensed bio-oil is highly complex as highlighted in several reviews [1,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The cellulosic and hemi-cellulosic fraction of pyrolysis oil vapors and condensed bio-oil is largely responsible for many of its adverse fuel properties and the high propensity for coke formation [1]. Studies on pyrolysis of cellulose and sugar-derived oxygenates coupled with gas or liquid chromatography (GC or LC) and mass spectrometry (MS) have shown how the small oxygenates formed during pyrolysis can undergo secondary polymerization reactions, forming larger molecules and eventually coke [17,18]. The composition of pyrolysis vapor and condensed bio-oil is highly complex as highlighted in several reviews [1,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the aforementioned limitations, an on‐line mass spectrometric analysis method published recently was employed to detect the initial products (i. e., the first products leaving the hot pyrolysis surface) of fast pyrolysis of lignin model compounds ranging from trimers to a polymer. We believe that this is the first time that the fast pyrolysis behavior of pure, nonderivatized lignin oligomers (larger than dimers) has been examined and reported.…”
Section: Introductionmentioning
confidence: 99%
“…Dramatic difference in biopolymer behavior on heated, structured surfaces is integral to reactor design for utilization of natural resources such as biomass. Industrial scale pyrolysis reactions are commonly carried out in the presence of pressed silica and alumina based catalysts with macropores 27 28 , while the majority of fundamental pyrolysis studies are carried out on smooth metal surfaces 4 6 . The impact of porous structures and dramatic role of temperature on the de-wetting liftoff behavior of cellulose at high temperature allows for tuning to increase heat transfer and dramatically alter the throughput of biomass reactors, which are overall heat transfer limited systems.…”
Section: Resultsmentioning
confidence: 99%
“…When subjected to high temperatures (>400 °C), long chain biopolymers such as cellulose decompose into smaller, more valuable products used for renewable fuels and chemicals. The chemistry of cellulose decomposition is the subject of ongoing investigation 1 2 3 4 ; promotion of the desirable reaction pathways and/or variation of the heating rate can strongly alter product distribution consisting of hundreds of chemicals 5 6 . Recent work has shown that long chain, crystalline cellulose reacts to a short-lived liquid intermediate with millisecond lifetime comprised of molten oligomers before decomposing to vapors 7 8 9 .…”
mentioning
confidence: 99%